The Effect of Metronome Application for Stabilizing Tempo in Singing at Elementary School - Utama, Aldi Rizki; Julia, Julia; Gusrayani, Diah (Jurnal Pena Ilmiah, 2019)
One of the problems in singing at elementary school is the skill students of stabilizing tempo, when the tempo becomes an important because it is one of the main elements in singing. Application metronome become alternative solution that teachers can use as learning media to stabilize singing tempo. The study aims to determine the difference in student skills to stabilize the singing tempo in experimental classes and control classes. The design of this research is a quasi-experimental with non-equivalent design control group. The samples on this study were 30 students of experimental class and 30 students of the control class. The results showed, the grades of students in the experimental class increased from 41.3 to 80.0, the grades of the studentsÂ  control grade from 46 to 61.3. However, based on statistical results, there are differences in improvements that show higher experimental class upgrades than the control class.